User experience design : creating designs users really love - Allanwood, Gavin, ....-; Beare, Peter, 1970- (London : Bloomsbury Academic, 2014)
User Experience (UX) and User Experience Design (UXD) challenge existing usability models by changing the emphasis from task and usage to a broader understanding of experience and purpose. UX techniques are gaining popularity across a range of current digital media design and development areas. Today's designers need to create work that will impact positively on everyone who is exposed to it, as work is delivered across diverse digital platforms accessible to huge populations. It may be passive and immutable or interactive and dynamic, but the success of the design will depend largely on how well the user experience is constructed.Basics Interactive Design 02: User Experience Design introduces an approach to graphic design that puts human experience at the forefront of the design process. Throughout the book, Gavin Allanwood and Peter Beare show how design skills can be improved by undertaking practical exercises and reviewing the work, style and motivations of leading practitioners.
Includes bibliographical references (pages 172-173) and index.
Keywords: Design -- Human factors; Design -- Methodology